Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/s41372-018-0205-9
|View full text |Cite
|
Sign up to set email alerts
|

Length of stay and cost of birth hospitalization: effects of subfertility and ART

Abstract: Maternal fertility group was not an independent predictor of infant LOS and costs. Prematurity and birthweight were driving factors in resource utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…The risk of neonatal mortality was not elevated. We also studied the length of birth hospitalizations and the costs of care incurred (79) and found that gestational age was an important factor in interfertility group differences. In stratified analyses, the most pronounced interfertility group differences were among the infants born at >37 weeks of gestation.…”
Section: Neonatal and Child Health Health Of Infants At Deliverymentioning
confidence: 99%
“…The risk of neonatal mortality was not elevated. We also studied the length of birth hospitalizations and the costs of care incurred (79) and found that gestational age was an important factor in interfertility group differences. In stratified analyses, the most pronounced interfertility group differences were among the infants born at >37 weeks of gestation.…”
Section: Neonatal and Child Health Health Of Infants At Deliverymentioning
confidence: 99%
“…Infertility is emerging as a growing major global reproductive health problem ( WHO, 2015 ; Baskaran et al ., 2019 ; Sun et al ., 2019 ; Sadeghi, 2020 ). The procedures of diagnostics and treatment of infertility are long term, complicated, highly expensive, and do not always end successfully ( Inhorn and Patrizio, 2015 ; Kissin et al ., 2016 ; Dukhovny et al ., 2018 ). Therefore, many infertile couples seek complementary and alternative medicines (CAM) for infertility treatment ( Smith et al ., 2010 ; Frass et al ., 2012 ; Ghazeeri et al ., 2012 ; Bardaweel et al ., 2013 ; Read et al ., 2014 ; Hwang et al ., 2019 ) to improve their chances of having a child.…”
Section: Introductionmentioning
confidence: 99%